Non Atrial Fibrillation related Central Retinal Artery Occlusion (CRAO) in Hyperthyroidism: A Case Report - Wawhal, Mahendra; Mogal, Vajed; Dalvi, Vishal; Sanap, Sandeep; Rathi, Amit (International Journal of Medical Research and Review, 2015)
We report a case of non AF related Central retinal artery occlusion (CRAO) (Stroke) in untreated & uncontrolled hyperthyroidism. CRAO can be considered as an ocular analogue of stroke or an ocular equivalent of acute myocardial infarction. Generally hyperthyroidism is associated with Stroke (CRAO) because of atrial fibrillation. However, we report a case of uncontrolled hyperthyroidism with CRAO in the absence of atrial fibrillation. It is with an intent to highlight the fact that a hyperthyroid state is not only complicated by AF, but even hyperthyroidism in itself is a potential risk factor in the causation of stroke.We came across only one case report of ischaemic stroke in a hyperthyroid patient without AF. We could not find any case report of hyperthyroidism with AF related CRAO in literature. Hence we report first case of non AF related CRAO in hyperthyroidism & perhaps second case report of non AF related stroke in hyperthyroidism in literature so far. An uncontrolled hyperthyroid state is tantamount to a sustained inflammatory state that results in endothelial dysfunction by causing hypercoagulable state culminating in a small caliber vessel blockage.